New Structural and Mechanistic Insights Into Functional Roles of Cytochrome b559 in Photosystem II - Chiu, Yi-Fang; Chu, Hsiu-An (Frontiers in Plant Science, 2022)
Cytochrome (Cyt) b559 is a key component of the photosystem II complex (PSII) in its assembly and proper function. Previous studies have suggested that Cyt b559 has functional roles in the early assembly of PSII and in secondary electron transfer pathways that protect PSII against photoinhibition. In addition, Cyt b559 in various PSII preparations exhibited multiple different redox potential forms. However, the precise functional roles of Cyt b559 in PSII remain unclear. Recent site-directed mutagenesis studies combined with functional genomics and biochemical analysis as well as high-resolution x-ray crystallography and cryo-electron microscopy studies of native, inactive and assembly intermediates of PSIIs have provided important new structural and mechanistic insights into the functional roles of Cyt b559. This mini-review gives an overview of these new exciting results and their significance for understanding the structural and functional roles of Cyt b559 in PSII.